2014
DOI: 10.1016/j.ijms.2013.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced dissociation mass spectroscopy of firefly oxyluciferin anions

Abstract: dissociation mass spectroscopy of firefly oxyluciferin anions, International Journal of Mass Spectrometry (2013), http://dx.doi.org/10.1016/j.ijms. 2013.11.012 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process error… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…Second, the f value of the neutral form is lower than that of the ionic form in both toluene and water such that the ionic form is necessary for high luminous efficiency. Third, the dominant fragment dissociated from oxyluciferin in firefly exists as an ion; therefore, it originates from the ionic form of oxyluciferin.…”
Section: Resultsmentioning
confidence: 99%
“…Second, the f value of the neutral form is lower than that of the ionic form in both toluene and water such that the ionic form is necessary for high luminous efficiency. Third, the dominant fragment dissociated from oxyluciferin in firefly exists as an ion; therefore, it originates from the ionic form of oxyluciferin.…”
Section: Resultsmentioning
confidence: 99%
“…Last, we comment on our failure to observe photofragmentation for any of the luciferin systems. A photodissociation mass spectrometry study on OxyLH − (and DMOxyL − ), including with synthetic isotopologues, found the dissociation threshold for the dominant fragment to be ≈1.86 eV, [48] substantially lower than the VDE and presumably also the adiabatic detachment energy. The major ion fragment at m/z =175 (com-pared with m/z =249 for parent OxyLH − ) should be detectable in our tandem IMS experiment.…”
Section: Discussionmentioning
confidence: 99%
“…17 Absorption cannot be measured directly but often relies on photodissociation, so-called action spectroscopy. 18,19 Interestingly, the most abundant photo-induced fragment ion is deprotonated 2-cyano-6-hydroxybenzothiazole, 20 the same intermediate in the postulated regeneration of luciferin from oxyluciferin in vivo in insects. A single water molecule was found to significantly blueshift the absorption (by about 0.23 eV).…”
Section: Introductionmentioning
confidence: 99%